Needs Analysis Of Arabic Balaghah Module Development Through Infographics - Abdul Rahman, Noor Eliza; Zainudin, Muhamad Amir; Abdul Hamid, Mohd Fauzi; Ab. Halim, Zulazhan; Abdullah, Abdul Hakim; Salleh, Abdul Wahid; Arifin, Zamri; Sardi Mohd Yusop, Janudin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The knowledge discipline of Arabic balaghah requires creative and innovative learning techniques to master it. Infographics are an alternative to making information or learning more concise, exciting, and easy to understand. Detailed information and learning content can be translated into graphics and summaries that engage students. This study was conducted to obtain students' views on the need to design and develop infographic modules to learn Arabic balaghah. Design and Development Research is used as the approach of this study. This study focused on the first phase, which needs analysis data using a set of questionnaires related to infographic design, infographic needs in achieving information, and infographic requirements in module content design. The subject is 136 Bachelor in Arabic Studies students who had taken the Balaghah Al-Qazwini Text Study course offered for the Bachelor of Arabic Studies Programme at Sultan Zainal Abidin University. Quantitative data were analyzed using Statistical Package for Social Science (SPSS) software to obtain percentages, means, and standard deviations. The results of the study found that there is a need to develop infographic modules to help students master the knowledge of balaghah more efficiently and systematically.